2019
DOI: 10.1093/qjmed/hcz157
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection and the risk of colorectal cancer: a nationwide population-based cohort study

Abstract: Background The role of Helicobacter pylori (H. pylori) infection in the development of colorectal neoplasia has been a matter of scientific debate with controversial findings. Aims This study examined the association between H. pylori infection and colorectal cancer (CRC) in a nationwide population-based Chinese cohort study. Methods A total of approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Our findings are consistent with the results of the positive association between serologic responses to H. pylori proteins and CRC (Butt et al, 2019;Epplein et al, 2013). The results are also consistent with the recent Meta-analyses confirmed the positive association between H. pylori infection and the development of CRC (Chen et al, 2013;Guo & Li, 2014;Hong et al, 2012;Rokkas et al, 2013;Wu et al, 2013;Yang et al, 2019;Zhao et al, 2016;Zhao et al, 2008;Zumkeller et al, 2006), and the findings of the original study in Germany (Zhang et al, 2012), in Korea (Park et al, 2018), and China (Liu et al, 2019). The available Meta-analysis by 2019 has not examined for the subgroups of distal and rectum cancers combined.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with the results of the positive association between serologic responses to H. pylori proteins and CRC (Butt et al, 2019;Epplein et al, 2013). The results are also consistent with the recent Meta-analyses confirmed the positive association between H. pylori infection and the development of CRC (Chen et al, 2013;Guo & Li, 2014;Hong et al, 2012;Rokkas et al, 2013;Wu et al, 2013;Yang et al, 2019;Zhao et al, 2016;Zhao et al, 2008;Zumkeller et al, 2006), and the findings of the original study in Germany (Zhang et al, 2012), in Korea (Park et al, 2018), and China (Liu et al, 2019). The available Meta-analysis by 2019 has not examined for the subgroups of distal and rectum cancers combined.…”
Section: Discussionsupporting
confidence: 92%
“…Although results from the previous studies on the association between H. pylori infection and CRC are inconsistent. This inconsistency could be attributable to the quality of the previous observational studies when the data related to the CRC of diet and nutrition and smoking status (IARC, 1986) was not included as confounding factor adjustment in the data analysis due to their limitation of the available database (Butt et al, 2019;Epplein et al, 2013;Liu et al, 2019;Park et al, 2018;Strofilas et al, 2012;Teimoorian et al, 2018).…”
Section: H Pylori Infection and Colorectal Cancers By Anatomical Locmentioning
confidence: 99%
“…pylori can produce bacterial urease, which hydrolyses in gastric luminal urea to form ammonia, which helps neutralize gastric acid and form a protective cloud around the organism, enabling it to penetrate the gastric mucus layer [25]. Several studies have reported an association between H. pylori infection and the incidence of gastric cancer and colorectal cancer [26,27]. Diagnostic testing for H. pylori includes endoscopic biopsy urease testing, urea breath testing, stool antigen assay, and serological ELISA testing [28].…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al [80] in 2017 studied that S. gallolyticus promoted cell proliferation and CRC development by increasing β-catenin signaling. A cohort study from Taiwan's National Health Insurance Research Database found that Helicobacter pylori infection was associated with increased risk of CRC (HR 1.87; 95% CI 1.37-2.57) [81]. Hypergastrinemia from chronic H. pylori infection leads to a mutagenesis.…”
Section: Streptococcus Gallolyticus and Helicobacter Pylorimentioning
confidence: 99%